Application of alternate healthy eating index to assess diet quality in male workers - Putri, Pramita Ariawati; Briawan, Dodik; Ekayanti, Ikeu (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
This study aimed to analyze diet quality of male workers. Study design was cross-sectional, involving 101 male workers of PT. Semen Indonesia Tuban, East Java aged 25-55 years old. Subjects were chosen using purposive sampling based on inclusion criterias. US adapted Alternate Healthy Index (AHEI) was used to assess diet quality that consists of 11 components. Components and portions were modified based on Indonesian Dietary Guidelines 2014. The result showed that grains and alcohol components had good score (10) and the lowest score was in sweetened beverages component (1.4). AHEI-score range from 45.1 to 95.7 and the mean was 69.5. More than half of workers (75.2%) diet quality was in need of improvement category (AHEI scores <76.2). Education level and working unit were correlated with diet quality (p<0.05). Workers diet quality in PT. Semen Indonesia Tuban needs to be improved.